Clearing space: Language reclamation, decolonization and the Internet. Issue 1 (1st August 2019) - Tcherneshoff, Kristen; Udell, Daniel Bögre
Perhaps the greatest misconception about cultural diversity is that the Internet has been a barrier to its sustenance by swallowing up smaller cultures in a torrent of English, Spanish and other mass media languages. However, the Internet has equipped people with the possibility of sustaining their ancestral tongues by expanding media access and creation, making it possible to use minoritized languages on a daily basis and promote them in a global context without external support. This article explores the historical relationship between language assimilation and colonization and, by extension, the central role that language reclamation plays in decolonization; and the recent groundswell of online language activism through geographically diverse case studies, including Tunica, Kernowek and Võro. This article initiates an unwritten history of language activism in the twenty-first century and demonstrates the foundation of a roadmap for leveraging the Internet in contemporary language revival.